Daylighting performance simulation and analysis of translucent concrete building envelopes. (July 2020) - Su, Xiaosong; Zhang, Ling; Liu, Zhongbing; Luo, Yongqiang; Lian, Jinbu; Liang, Ping
Abstract: A novel optical fiber (OF) embedded building envelope, namely translucent concrete (TC), was proposed and popularized for its light transmission property and unique artistic features, but there is still a lack of in-depth research on its daylighting performance analysis. To reveal the impacts of multi-factors on TC daylighting performance, an optical model of TC was established based on a ray-tracing method. In the model validation, both the simulated transmittance of OFs and illuminance of translucent concrete were in a good agreement with the experimental results. The simulation results showed when the numerical aperture (NA) of the OFs increased from 0.51 to 0.70, the annual average luminous flux of TC under seven cities conditions could be enhanced by up to 40.62%. In terms of effective illuminance, the optimum fiber volume ratio of the seven cities was determined, respectively. Besides, it was found that the core-cladding interface losses could lead to a relative deviation over 5% when the length of 1-mm OFs with 0.51 NA exceeded 259 mm, and the deviation could be larger with the decrease in diameter of OFs and the increase both in length and NA of OFs. Highlights: A ray-tracing method for calculating the transmittance of optical fiber was developed and verified. A daylighting model of translucent concrete building envelope was established and verified. The relationship among the optimum tilt angle, numerical aperture and local latitude was investigated. A comparison between the proposed model with the ideal model was conducted. A ternary linear regression equation for predicting the optimum tilt angle of translucent concrete was proposed.